Synchronous collaborative application of nuclear power engineering design platform - Zhihua ZENG; Delong YI; Yan LI (Dianxin kexue)
At present,the nuclear power business shows the development trend of multi-route,multi-base develop-ment trend.Coupled with the huge workload of nuclear power engineering design and the fine division of labor cha-racteristics,the relevant professional in different places appears more and more cross-design in the nuclear power en-gineering design,resulting in the frequency of funding becoming more and more dense between the various profes-sional.How to shorten the synchronization time of engineering design data between different places,and even achieve real-time synchronization of engineering design data is worth to study in the field of collaborative design of nuclear power projects.From the point of view of system verification,the existing popular virtualization technology was used to carry out an in-depth exploration and verification on the synergetic synergy of nuclear power engineering design,and a set of auxiliary access platform was added on the basis of the original design platform structure to real-ize remote user access and collaborative design of nuclear power projects.The research results have guiding signific-ance for the follow-up design and production platform upgrade and optimization.